Questions and Challenges in the Development of Mesenchymal Stromal/Stem Cell-Based Therapies in Veterinary Medicine - Devireddy, Lax R.; Boxer, Lynne; Myers, Michael J.; Skasko, Mark; Screven, Rudell (Tissue engineering. Part B, Reviews, 2017)
The therapeutic potential of stem cells has fascinated those interested in treating diseases in both human and animal subjects. Although the exact mechanism of action and the definitive effectiveness of stem cell therapies remain unclear, animal owner perceptions and a desire for improved treatment options have fueled the interest of clinicians and stakeholders. Standards do not yet exist to define the critical attributes of mesenchymal stem/stromal cell (MSC)-based products derived from veterinary species such as the dog, cat, and horse. This has led veterinary stakeholders to adopt those guidelines and criteria set forth for human MSC-based products; however, these criteria are not always applicable to MSCs from dogs, cats, and horses (e.g., variability in species-specific cell surface marker expression and antibody cross reactivity). Establishing useful standards and meaningful product quality criteria as well as the understanding of full spectrum of MSC functions and preclinical evidence for safety and therapeutic efficacy for veterinary (companion and recreational animals) MSC-based-products will be critical to furthering product development, and may ultimately facilitate the availability of FDA-approved MSC-based products for use in veterinary medicine.